Assessment of attentional abilities in male volleyball athletes - Wilson, V. E.; Ainsworth, M.; Bird, E. I. (International Journal of Sport Psychology, 1985)
Nationally ranked male volleyball players (N = 11) were dichotomized into "good" and "poor" concentrators by their head coach. A number of tests were performed: the Test of Attentional and Interpersonal Style (TAIS), an EEG, the Stroop Test, a video game "Space Eggs," and the Profile of Mood States (POMS). Demographic data were also obtained. The good concentrators were shown to have a more narrow internal and external focus of attention as measured by the TAIS than the poor concentrators. Good concentrators also had lower EEG readings in baseline and recovery phases but not during testing situations. No other measures were significant. Implication: Good concentrators appeared to have a narrower focus of attention and an ability to maintain a more relaxed brain state at rest. Concentration, as perceived by a highly qualified coach, is highly related to focus of attention in male volleyball players.